The Effect of Problem Based Learning Model and Learning Interest on Critical Thinking in Islamic Cultural History - Eri Kusumawati; Choirudin Choirudin; M. Saidun Anwar (CV. Bimbingan Belajar Assyfa, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model and learning interest on students' critical thinking skills in the subject of Islamic Cultural History (SKI) at MA Al Huda Tulung Balak. This research is motivated by the low level of students' critical thinking skills caused by the use of conventional teaching methods and low student learning interest. This study employed a quantitative approach using a quasi-experimental method with a 2×2 factorial design. The population consisted of all twelfth-grade students at MA Al Huda Tulung Balak, with a sample of 60 students divided into experimental and control groups. Data were collected through tests, questionnaires, and observations. The research instruments included a critical thinking test (10 essay questions), a learning interest questionnaire (25 items), and an observation sheet. Data analysis was conducted through prerequisite tests (normality and homogeneity) and hypothesis testing using Two-Way ANOVA. The results showed that: (1) the PBL model had a significant effect on students' critical thinking skills (Sig = 0.000 < 0.05); (2) learning interest had a significant effect on students' critical thinking skills (Sig = 0.002 < 0.05); and (3) there was a significant interaction between the PBL model and learning interest on students' critical thinking skills (Sig = 0.011 < 0.05). The mean score of critical thinking skills in the experimental class (82.40) was higher than in the control class (73.10). In conclusion, the implementation of the PBL model supported by high learning interest can improve students' critical thinking skills in Islamic Cultural History.